\(\displaystyle\frac{{\left.{d}{x}\right.}}{{\left.{d}{t}\right.}}={4}{t},\frac{{\left.{d}{y}\right.}}{{\left.{d}{t}\right.}}={2}{t}-{4},\frac{{\left.{d}{z}\right.}}{{\left.{d}{t}\right.}}={3}.\ {A}{t}\ {t}={1}:\frac{{\left.{d}{x}\right.}}{{\left.{d}{t}\right.}}={4},\frac{{\left.{d}{y}\right.}}{{\left.{d}{t}\right.}}=-{2},\frac{{\left.{d}{z}\right.}}{{\left.{d}{t}\right.}}={3}.\)

In the direction i-3j+2k the components of the velocity would be (4,6,6).

In the direction i-3j+2k the components of the velocity would be (4,6,6).